2012
DOI: 10.1007/s00253-011-3854-6
|View full text |Cite
|
Sign up to set email alerts
|

Pressure to kill or pressure to boost: a review on the various effects and applications of hydrostatic pressure in bacterial biotechnology

Abstract: Much knowledge has been gained for the last 30 years about the effects of pressure on bacteria, and various pressure-based technologies have been designed. The development of modern molecular biology techniques (e.g., DNA microarrays) as well as the technological advances realized in the manufacturing of robust sampling and high-pressure devices has allowed these advances. Not only the direct effects on cell components (membranes, proteins, and nucleic acids) have been unraveled, but also the cellular response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 112 publications
(116 reference statements)
0
33
0
1
Order By: Relevance
“…HHP in DSSs is at approximately 10-50 MPa at 1000-5000 m respectively, with an increase of 10 MPa km −1 , and temperature is 2-3°C (Nagata et al, 2010). HHP is used to increase yield in biotechnological applications by enhancing oxygen rate in high-density bioreactors (Follonier et al, 2012). Nonetheless it has also been shown to reduce poly-β-hydroxybutyric acid degradation by deep sea fungi (Gonda et al, 2000).…”
Section: Degradation Of Pahs Under Hydrostatic High Pressure (Hhp) Anmentioning
confidence: 98%
See 1 more Smart Citation
“…HHP in DSSs is at approximately 10-50 MPa at 1000-5000 m respectively, with an increase of 10 MPa km −1 , and temperature is 2-3°C (Nagata et al, 2010). HHP is used to increase yield in biotechnological applications by enhancing oxygen rate in high-density bioreactors (Follonier et al, 2012). Nonetheless it has also been shown to reduce poly-β-hydroxybutyric acid degradation by deep sea fungi (Gonda et al, 2000).…”
Section: Degradation Of Pahs Under Hydrostatic High Pressure (Hhp) Anmentioning
confidence: 98%
“…As an acclimation reaction, bacteria alter their membrane composition and synthesize protective cold-shock proteins (Barria et al, 2013). Monomeric proteins are generally well preserved by HHP, while pressure can affect the supramolecular configuration and catalytic site of polymeric enzymes and, consequently, reduce substrate affinity (Eisenmenger and Reyes-De-Corcuera, 2009;Follonier et al, 2012). In dioxygenases (a polymeric enzyme), HHP can induce the release of iron from Fe-S clusters (Malone et al, 2006).…”
Section: Degradation Of Pahs Under Hydrostatic High Pressure (Hhp) Anmentioning
confidence: 99%
“…Additionally, this pressure range may be applied aiming at the disintegration of plant materials. Possible mechanisms reported for the disintegration of microbial and plant cells are a pressure-induced denaturation of membrane proteins (Kato et al, 2002;Ulmer et al, 2002;Winter & Jeworrek, 2009), increased activity of degrading enzymes , cell wall stress, excessive mechanical strain of the membrane (Hartmann & Delgado, 2004), as well as altered membrane fluidity and permeability due to phase transition of the phospholipid bilayer (Follonier et al, 2012;Winter et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…It is reported that HHP at pressures higher than 300 MPa causes irreversible protein denaturation and induces cell death through a necrotic-like pathway [Diehl et al, 2008;Rivalain et al, 2010]. As for the effect of HHP on enzymes, HHP at 100- inactivation [Diehl et al, 2008;Rivalain et al, 2010;Follonier et al, 2012]. However, for some proteases, proteolysis enhancement through HHP at pressures of up to 400 MPa was observed, depending on substrate changes and not on enzyme changes [Chicón et al, 2006].…”
Section: Discussionmentioning
confidence: 99%